2019
DOI: 10.1002/bsd2.76
|View full text |Cite
|
Sign up to set email alerts
|

A qualitative study of Argentine small and medium enterprises: Factors driving social responsibility

Abstract: Small and medium‐sized enterprise (SMEs) social responsibility has recently begun to gain greater importance in Argentina due to a variety of contextual factors. The main area of inquiry investigated in this study was the motivation for adopting social responsibility initiatives at Argentine SMEs. Exploratory, qualitative methods were employed to evaluate social responsibility initiatives at six firms across several industries. Semistructured interviews served as the primary source of data. Data were analyzed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 46 publications
0
4
0
Order By: Relevance
“…South America, Africa, and Asia are some examples of continental synonymic terms use instead of “DO” without specific reference to their sub‐contextual nation states or regional blocks. This disregard of continental sub‐contexts may explain DCSR’s plateau given the vagueness that accompanies analyzes that focus on continents at the macro‐aggregate level of analysis (Colaço & Simão, 2018; Massoud et al., 2020; Vincent et al., 2019).…”
Section: Results: Diagnostic Presentation and Discussionmentioning
confidence: 99%
“…South America, Africa, and Asia are some examples of continental synonymic terms use instead of “DO” without specific reference to their sub‐contextual nation states or regional blocks. This disregard of continental sub‐contexts may explain DCSR’s plateau given the vagueness that accompanies analyzes that focus on continents at the macro‐aggregate level of analysis (Colaço & Simão, 2018; Massoud et al., 2020; Vincent et al., 2019).…”
Section: Results: Diagnostic Presentation and Discussionmentioning
confidence: 99%
“…Stakeholder pressures refer to organizations' concerns about the expectations of and the requirements for SSP adoption from individual stakeholders (Govindan et al, 2020;Massoud et al, 2020).…”
Section: Stakeholder Theorymentioning
confidence: 99%
“…Stakeholder pressures refer to organizations' concerns about the expectations of and the requirements for SSP adoption from individual stakeholders (Govindan et al, 2020; Massoud et al, 2020). Among them, government, laborers, market, and suppliers are the most prominent in exerting pressures, tangible and intangible alike, on companies to adopt SSP (Sodhi et al, 2022; Tran et al, 2021).…”
Section: Theoretical Background and Hypothesis Developmentmentioning
confidence: 99%
See 1 more Smart Citation
“…A comprehensive review of existing literature has revealed that enterprises operating within the same geographical location are subject to isomorphic pressures and tend to engage in similar CSP (Marquis and Tilcsik, 2016;Massoud et al, 2020). These enterprises are bound by a unique social activity that is specific to their respective locations and communities, owing to similarities in economic, regulatory, and legal environments (Ding et al, 2019).…”
Section: Firm Location Corporate Social Performance and Multi-nationa...mentioning
confidence: 99%